2016
DOI: 10.1038/srep21716
|View full text |Cite
|
Sign up to set email alerts
|

The role of WWOX polymorphisms on COPD susceptibility and pulmonary function traits in Chinese: a case-control study and family-based analysis

Abstract: Single nucleotide polymorphisms (SNPs) in the WW domain containing oxidoreductase (WWOX) gene were recently identified to be quantitative trait loci for lung function and thus likely to be susceptible biomarkers for COPD. However, the associations between WWOX SNPs and COPD risk are still unclear. Here, by conducting a two-center case-control study including 1511 COPD cases and 1677 controls and a family-based analysis comprising 95 nuclear pedigrees, we tested the associations between five SNPs that are rs102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The molecules involved in these reactions determine the susceptibility of COPD. Studies have shown that cigarette smoking is a main risk factor for COPD, and the interaction between genes and smoking is related to lung function in COPD 21,22. In our study, we found that smoking was closely related to the general characteristics of COPD patients and the polymorphism of GSTP1, HO-1, and SOD3 is correlated with the occurrence of COPD, but there is no correlation with the different stages of COPD.…”
Section: Discussionsupporting
confidence: 45%
“…The molecules involved in these reactions determine the susceptibility of COPD. Studies have shown that cigarette smoking is a main risk factor for COPD, and the interaction between genes and smoking is related to lung function in COPD 21,22. In our study, we found that smoking was closely related to the general characteristics of COPD patients and the polymorphism of GSTP1, HO-1, and SOD3 is correlated with the occurrence of COPD, but there is no correlation with the different stages of COPD.…”
Section: Discussionsupporting
confidence: 45%
“…It has been reported that SNP may exert a modifying on gene expression and is associated with the risk of breast and ovarian carcinogenesis 12 . Xie et al found that G>T in WWOX SNP rs383362 is related to an elevated risk of developing chronic obstructive pulmonary disease in a T allele-number dependent-manner 13 . Furthermore, WWOX genetic variants were reported to be correlated with cancer susceptibility and prognosis 14 - 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic components associated with COPD risk should also be seriously considered for the fact that only a fraction of smokers ever developed COPD . Indeed, a growing number of studies, most prominent of which are the genome‐wide association studies (GWASs), have broadly identified an abundance of genetic variants that are single‐nucleotide polymorphisms (SNPs), to be associated with COPD susceptibility or some phenotypes of COPD …”
Section: Introductionmentioning
confidence: 99%
“…3 Indeed, a growing number of studies, most prominent of which are the genome-wide association studies (GWASs), have broadly identified an abundance of genetic variants that are single-nucleotide polymorphisms (SNPs), to be associated with COPD susceptibility or some phenotypes of COPD. [4][5][6][7] Despite the unprecedented success achieved in identifying genetic variants associated with COPD risk or lung function, these commonly causal SNPs with minor allele frequency (MAF > 5%) only explained a small fraction of expected heritability of human diseases. 8,9 Common SNPs cannot account for all of the heritability of diseases, thus we still need to make great effort in discovering untapped heritability as a person's susceptibility to disease depends on a combined effect of all disease associated variants.…”
Section: Introductionmentioning
confidence: 99%